Influence of audience feedback on editorial decisions of local digital newspapers: a comparative study between Chile, Peru and Colombia - Greene González, María Francisca (2024)
This comparative study analyzes fifteen local digital newspapers from Chile, Peru and Colombia with the objective of investigating how audience feedback influences editorial decisions. A qualitative methodology was used based on semi-structured interviews carried out with editors of the most read Web portals in the five cities with the largest population in each country. The most notable results reveal notable similarities between the media of each nation, evidencing a strong influence of audience feedback on editorial decisions, changes in business models from digital transformation and the use of tools for measuring results, collection of insights and contact with users. This finding suggests the importance of understanding and responding to audience preferences and opinions for local digital media in the region, highlighting the need for editorial strategies that encourage audience participation and engagement.